2015
DOI: 10.3390/rs70810917
|View full text |Cite
|
Sign up to set email alerts
|

Use of the Standardized Precipitation Evapotranspiration Index (SPEI) to Characterize the Drying Trend in Southwest China from 1982–2012

Abstract: Abstract:In this study, the Standardized Precipitation Evaporation Index (SPEI) was applied to characterize the drought conditions in Southwest China from 1982-2012. The SPEI was calculated by precipitation and temperature data for various accumulation periods. Based on the SPEI, the multi-scale patterns, the trend, and the spatio-temporal extent of drought were evaluated, respectively. The results explicitly showed a drying trend of Southwest China. The mean SPEI values at five time scales all decreased signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
75
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 121 publications
(78 citation statements)
references
References 59 publications
3
75
0
Order By: Relevance
“…For example, Hu and Willson () and Sun et al (), Sun, Chen, Ju, et al () have reported that the impact of ET 0 on drought could be equivalent to or even higher than that from precipitation. Consequently, understanding the spatial and temporal variations in ET 0 is a vital component for comprehensively understanding hydrometeorological changes and is helpful for better monitoring and predicting drought (Beguería, Vicente‐Serrano, Reig, & Latorre, ; Li, He, Quan, Liao, & Bai, ; McEvoy, Huntington, Mejia, & Hobbins, ; Sun et al, ; Sun, Chen, Sun, et al, ; Vicente‐Serrano, Beguería, & Lópezmoreno, ; Zhang et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…For example, Hu and Willson () and Sun et al (), Sun, Chen, Ju, et al () have reported that the impact of ET 0 on drought could be equivalent to or even higher than that from precipitation. Consequently, understanding the spatial and temporal variations in ET 0 is a vital component for comprehensively understanding hydrometeorological changes and is helpful for better monitoring and predicting drought (Beguería, Vicente‐Serrano, Reig, & Latorre, ; Li, He, Quan, Liao, & Bai, ; McEvoy, Huntington, Mejia, & Hobbins, ; Sun et al, ; Sun, Chen, Sun, et al, ; Vicente‐Serrano, Beguería, & Lópezmoreno, ; Zhang et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…As a result of its unique topography and geographical location, this region is considered to be of great important in research on global climate change. Many studies have reported that Sichuan has experienced a serious drying trend during the past few decades and its natural environment is fragile (Thomas, 2000;Zhai et al, 2005;Qin et al, 2010;Li et al, 2015). Meteorological stations are irregularly spaced in this region and are especially sparse in the mountainous and highland areas, which could lead to spatial inconsistencies and uncertainties in climate studies.…”
mentioning
confidence: 99%
“…The non-normal distribution of atmospheric and hydrological variables makes the classical statistical methods invalid, however, the non-parametric test method is considered as a good tool for trend analysis. The M-K test has the advantage of the independent of data distribution and less sensitive to missing values and thus most commonly used for assessment of trends in different climate and hydrological variables [47].…”
Section: Mann-kendall Trend Testmentioning
confidence: 99%
“…Based on the above advantages, it has been widely used in different countries and regions over the world [8,[44][45][46], showing a good performance on drought analysis. For China, Li et al [47] compared the SPEI and the SPI for drought analysis and indicated that the SPEI could better monitor the drought conditions than SPI in months with significant increase of temperature. Shi et al [48] showed that the SPEI values effectively reflected the spatial and temporal pattern of drought occurrence in Henan Province.…”
Section: Introductionmentioning
confidence: 99%